Inequities in the continuum of maternal care in Mexico: trends before and after COVID-19 - Edson Serván-Mori; Rocio Garcia-Diaz; Sergio Meneses-Navarro; Octavio Gómez-Dantés; Diego Cerecero-García; Arachu Castro; Rafael Lozano (International Journal for Equity in Health)
Abstract Background Despite progress in maternal health coverage in Mexico, inequities persist, particularly in postnatal care. The COVID-19 pandemic further widened these gaps, disproportionately affecting women with similar health needs but different socioeconomic conditions. This study assesses trends in maternal healthcare coverage and inequity across nine stages of antenatal, delivery, and postnatal care, comparing pre- and post-pandemic periods. By examining horizontal inequity, we identify critical gaps and policy implications to enhance equitable maternal healthcare access. Methods We conducted a population-based, pooled cross-sectional and retrospective analysis for the last three decades, using data from the five waves (1997, 2009, 2014, 2018, and 2023) of the Mexican National Survey of Demographic Dynamics (ENADID). Our study included 123,197 Mexican women aged 12–54 with recent live births, representing a population of 38.5 million. We estimated coverage for antenatal and postnatal care stages. We used multiple regression models to assess factors influencing the likelihood of receiving comprehensive antenatal care, skilled delivery care and postpartum care interventions, both pre-and post-COVID-19. We estimated horizontal inequity using concentration index and decomposition analysis to highlight disparities among women with similar needs and examine how these disparities have changed due to COVID-19 across nine antenatal, delivery, and postnatal care stages. Findings Full antenatal and postnatal health care in Mexico was inadequate and inequitable. Only 73% of pregnant women received timely antenatal care and 88.3% received frequent care, despite 97.9% claiming to have received some care. Inadequate care was linked to lower education, labour market participation, low socioeconomic status, higher parity, and rural residency. The most inequitable aspects are access to skilled and institutional health care and timely post-partum care. The dismantling of a public health insurance system and focused strategies that incentivized the use of maternal health services during the pre-COVID period (January 2019 to March 2020) led to significant health coverage losses, exacerbating horizontal inequity in these areas. Although high equity was achieved in comprehensive antenatal healthcare from 2009 to 2023, since COVID, inequity has increased, particularly in antenatal indicators such as receiving four or more antenatal check-ups and check-ups in the first trimester. The pandemic intensified these inequities, and the values of these indicators have not returned to pre-pandemic levels, underscoring the seriousness of the situation. Conclusions Despite efforts to improve maternal care, comprehensive antenatal services reach only 61.8% of women in Mexico. This stresses not only the need for targeted policies to enhance antenatal, delivery, and postnatal coverage at critical stages of care, but also the need to continue strengthening strategies that have rendered good results, and not to eliminate them simply for political-ideological reasons. It is imperative to prioritize reducing existing inequalities within the population, as horizontal inequity reveals significant barriers preventing equitable access to maternal health services among women with similar needs. The most pronounced disparities exist in timely healthcare access, skilled deliveries, and institutional postnatal care, where systemic issues and financial constraints are particularly impactful. Addressing these inequities is essential not only to improve overall maternal health outcomes but also to ensure that all women can benefit from the full spectrum of maternal care, particularly in situations of health crisis, such as pandemics.